An atypical lower limb pain revealing a possible systemic venous vasculitis. Issue 2 (24th April 2020) - de Moreuil, Claire; Rouvière, Bénédicte; Rezig, Schéhérazade; Le Duc‐Pennec, Alexandra; Quintin‐Roué, Isabelle; Bressollette, Luc; Hoffmann, Clément
Abstract: We describe a possible systemic vasculitis involving electively large veins. The patient presented with severe febrile lower limb pain. Diagnosis was made by color Doppler ultrasound (CDU) and confirmed by anatomopathological examination of the long saphenous vein, but not by examination of the temporal artery which was normal. CDU found a unilateral halo sign of one temporal artery and a major wall swelling of the lower limb proximal deep veins. The etiology of this possible vasculitis is still unknown. It could be an unusual clinical presentation of giant cell arteritis with vein involvement but without proven arterial involvement. To confirm this hypothesis, it would be interesting to look systematically for lower limb vein thickening with CDU in patients newly diagnosed with giant cell arteritis who have lower limb pain.